Molecular phylogeny of Thraupis Boie, 1826 (Aves: Passeriformes) and taxonomic review of the Thraupis episcopus (Linnaeus, 1766) - Thraupis sayaca (Linnaeus, 1766) species complex - Castro, Diego Alejandro Cueva (2018)
Currently, the genus Thraupis Boie, 1826 is a monophyletic group with seven species, all of which have high molecular and morphological support. Nevertheless, the phylogenetic relationship of the species still unclear: T. abbas is the sister species of T. ornataT. palmarum clade, and a second group within the genus is composed by the T. episcopusT. sayaca clade. Furthermore, in the remaining species group, one of the species, T. glaucocolpa, has not been included in any of the previous molecular studies, even it was believed to be close related with T. sayaca. Moreover, the last species within the genus, T. cyanoptera, has an uncertain position in the genus phylogenetic tree. The T. episcopusT. sayacaT. galucocolpa species complex includes 18 subspecies and a high morphological variation and a wide distribution which includes overlapping zones of T. episcopus and T. sayaca, makes taxa identification almost impossible. Nonetheless, previous molecular studies had only used samples from two individuals of T. episcopus and one of T. sayaca. Furthermore, the group does not have taxonomic stability, as shown by the multiple changes, which occur at different levels: moving from one genus to another or from species to subspecies level etc. To check the genus, I analyze 1171 specimens. The morphometric analysis outcomes show the weight as the most variable and important measure and T. cyanoptera as the only clearly different species within taxonomic units. Finally, I did a phylogenetic analysis based on two mitochondrial genes (Cyt- and ND2), in addition to three nuclear introns (intron 3 of MUSK gen, intron 5 of TGFB2 gen and a piece of the intron 5 of the BF5 gen). I performed the extractions from tissues collected at different localities around the natural distribution of the species, with emphasis on T. episcopus and T. sayaca. I ran independent locus RAxML analysis and haplotypes networks and used to group the samples on genetic taxonomic units. RAxML and haplotypes analysis shows a close relationship between T. episcopus and T. sayaca with high probably introgression process within. Furthermore, exposed a genetic structure within T. episcopus. I used this genetic taxonomic units to ran a multilocus species tree with a calibrated molecular clock. The species tree suggests that the origin of the genus Thraupis was between 5.5 and 7.5 million years before present, in the Messinian age. Also recovers T. glaucocolpa is the oldest linage in the genus and shows a relation between the morphological traits with the genetic structure within T. episcopus. Finally, I suggest synonymizing several subspecies and elevating to species level the subspecies T. episcopus cana, based on the morphological and molecular data.